Municipality-Level Source Apportionment of PM2.5 Concentrations based on the CAPSS 2016: (IV) Jeollabuk-do - Kim, Eunhye; You, Seunghee; Bae, Minah; Kang, Yoon Hee; Son, Kyuwon; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
The observed annual mean PM2.5 concentration in Jeonbuk in 2016 was 31 μg/m3, twice higher than the national ambient air quality standard (15 μg/m3). In this study, we analyzed the self- and inter-provincial contributions to the PM2.5 concentrations in Jeonbuk by applying the Comprehensive Air quality Model with eXtensions with Particulate Source Apportionment Technology (CAMx-PSAT). The foreign contributions to the annual PM2.5 concentrations ranged from 13.1 to 17.3 μg/m3 in the fourteen local authorities in Jeonbuk. The domestic contributions in the local authorities calculated by adding the self-contributions and neighboring provincial contributions ranged from 5.9 to 12.0 μg/m3. It implies that both the foreign and domestic emissions are important to alleviate the PM2.5 concentrations in Jeonbuk. On top of the selfcontributions of Jeonbuk, the contributions of Chungnam and Jeonnam in the vicinity played significant roles in determining the annual mean PM2.5 concentrations in Jeonbuk. Meanwhile, it was estimated that daily PM2.5 concentrations in Jeonbuk can be decreased by up to 15 μg/m3 by controlling the nationwide emissions, especially when the daily PM2.5 concentration is higher than 50 μg/m3. It is noticed that the portion of inorganic ions in the domestic contributions increased as high as 90% when the daily mean PM2.5 concentrations in Jeonbuk increased. Accordingly, reductions of the precursor emissions such as SO2, NOx, and NH3 would be effective to decrease the occurrences of high PM2.5 days (>50 μg/m3) in Jeonbuk. The site-by-site model performance evaluations show that there still exist uncertainties in the emissions used in this study. Therefore, prior to developing a comprehensive air quality improvement plan in Jeonbuk, the preparation of local emissions able to explain the details of local air quality is required.
Keywords: Foreign contribution; Jeonbuk; Neighbor contributions; PM2.5; Self-contribution